Clinical observation of laparoscopic sleeve gastrectomy and metformin treatment in obese PCOS patients: Laparoscopic Sleeve Gastrectomy and Metformin in PCOS Obese - Ma, Qingya; He, Xiaojing; Fu, Zijie; Ren, Xiaodong; Sun, Ranran; Zhu, Siqi; Li, Xiaodong; Bian, Yahui (Journal of Medical Biochemistry, 2023)
Background: to observe the basic metabolic characteristics of obese patients with PCOS, and observe and compare the effect of laparoscopic sleeve gastrectomy and metformin treatment after 3 months. Methods: In January to December 2018, the Second Hospital of Hebei Medical University selected 104 women who were classified as obese with a BMI of 28kg/cm2 or higher and had PCOS. They were divided into obese PCOS group (53 cases) and obese non-pcos group (51 cases). Results: 1. There was no significant difference in waist circumference and WHR between patients who are obese with PCOS and patients who are obese without PCOS (P > 0.05).Obese PCOS patients were significantly higher in AMH, LH/FSH, T, FAI, homa-ir, TG, LDL, apo-b and uric acid than the group of non-PCOS patients who were obese. (P<0.05). The SHBG levels of obese patients with PCOS were obviously lower when contrasted with the levels in obese patients without PCOS (P < 0.05). 2. Body weight, BMI, INS, homa-ir and TG of obese PCOS patients were significantly decreased 3 months after laparoscopic sleeve gastrectomy compared with that before surgery (P < 0.05). After three months of medical treatment with metformin, the patients’ HOMA-IR was obviously reduced when contrasted with the pre-treatment HOMA-IR levels (P < 0.05), and there was no significant difference in the improvement degree of homa-ir between the two groups (P > 0.05). Conclusion: 1. Obese patients with PCOS demonstrated higher expression of AMH, LH/FSH, T, SHBG, and FAI when contrasted with the control group. Additionally, they experienced more severe insulin resistance and lipid metabolism disorders. 2. The weight and BMI of obese PCOS patients were significantly decreased after weight loss, while IR and blood lipid were significantly improved, while IR was improved in metformin group, and no significant discrepancy was observed in the degree of improvement of insulin resistance between both groups.